Effects of single-task, dual-task and successive physical-cognitive training on fall risk and balance performance in older adults: A randomized trial - Ataş Balcı, Leyla; Soğukkanlı Kadak, Kübra; Erdoğan, Sinem Burcu; Hanoğlu, Lütfü (My University, 2022)
Purpose: This study aimed to examine the effects of single-task, dual-task and successive physical-cognitive training on fall risk, balance, and gait performances in elderly.Methods: A total of 45 healthy older adults (73.0±4.6 years; 6 male and 39 female) underwent one of three interventions 3 times a week for 4 weeks. Group-1 performed single-task balance and gait exercises. Group-2 performed cognitive activity, balance, and gait exercises simultaneously. Group-3 performed successive cognitive activities and balance and gait exercises. Gait speed under single-task and dual-task conditions, Berg Balance Scale, Timed up and Go test, and Tinetti's Falls Efficacy Scale scores were evaluated before and after 4 weeks of interventions.Results: Gait speed under single-task condition, Timed up and Go Test, and Berg Balance Scale scores were improved in all groups (p<0.05). Gait speed under dual-task condition was improved in Groups-2 and 3 (p<0.05). Group-3 had greater improvement in Berg Balance Scale and Timed up and Go test scores than Group-2. Tinetti's Falls Efficacy Scale was improved in Group-1 and 3 after training while the improvement was greater in Group-3 (p=0.001).Conclusion: The present study suggests that an intervention involving cognitive and physical activities results in greater improvement in gait speed than interventions involving physical activities alone. However, successive physical-cognitive training may be more effective in reducing fear of fall and improving balance skills in elderly.

Amaç: Bu çalışma, tek görev, çift görev ve ardışık fiziksel-bilişsel eğitimin yaşlı erişkinlerde düşme riski, denge ve yürüme performansları üzerindeki etkilerini incelemek amacıyla yapıldı.Yöntem: Toplam 45 sağlıklı yaşlı yetişkine (73,0±4,6 yıl; 6 erkek ve 39 kadın) haftanın 3 günü 4 hafta üç müdahaleden biri uygulandı. Grup-1’e tekli görev denge ve yürüyüş egzersizleri yaptırıldı. Grup-2 eş zamanlı olarak bilişsel aktivite, denge ve yürüyüş egzersizleri yaptı. Grup-3 birbirini takip eden bilişsel aktiviteler, denge ve yürüyüş egzersizleri gerçekleştirdi. Dört haftalık müdahalelerden önce ve sonra tek ve çift görev koşullarında yürüyüş hızı, Süreli Kalk Yürü Testi, Berg Denge Ölçeği ve Tinetti'nin Düşme Etkinlik Ölçeği puanları değerlendirildi.Bulgular: Tüm gruplarda tek görev koşulu altında yürüyüş hızı, Berg Denge Ölçeği ve Süreli Kalk Yürü Testi puanları düzeldi (p<0,05). Grup 2 ve 3'te çift görev koşulu altında yürüyüş hızı düzeldi (p<0,05). Grup-3’ün, Süreli Kalk Yürü Testi ve Berg Denge Ölçeği puanlarında Grup-2'den daha fazla düzelme görüldü. Tinetti'nin Düşme Etkinlik Ölçeği puanları, Grup-1 ve 3'te düzelirken, Grup-3'te düzelme daha yüksekti (p=0,001).Sonuç: Bu çalışma yürüyüş hızında, bilişsel ve fiziksel aktiviteleri içeren bir müdahalenin, sadece fiziksel aktiviteleri içeren müdahalelere göre daha fazla düzelmeye yol açtığını göstermektedir. Birbirini takip eden fiziksel-bilişsel eğitim, denge becerilerini geliştirme ve yaşlılarda düşme korkusunu azaltmada daha etkili olabileceği düşünüldü.
Yaşlı bireylerde tek-görev, çift-görev ve ardışık fiziksel-bilişsel eğitimin düşme riski ve denge performansı üzerine etkileri: Randomize çalışma
Keywords: Falls; Exercise; Postural Balance; Aged; Gait; Düşmeler; Egzersiz; Postüral Denge; Yaşlı; Yürüyüş